Salafi Puritanism in Indonesia - Ahmad Syamsir; Muhammad Andi Septiadi; Muhamad Ilham Nurhakiki; Muhammad Ihsan al-Habsy; Muhammad Rizal Arifin Hidayah (International Journal of Islamic Khazanah, 2021)
Salafis are known for their puritanical attitudes and thoughts. They strongly desire to purify Islamic teachings by inviting people to avoid shirk, heresy, and superstition. This makes them trapped in these stigmas, thus making them often come into conflict with groups that are opposite to them. Especially when this Salafi understanding came to Indonesia, when they began to spread his puritanical teachings, they were immediately rejected. This study aims to understand the theological instructions adopted by Salafi figures both abroad and domestically. This type of research is qualitative by using secondary data sources and using the Geisteswissenschaften analysis technique developed by Wilhelm Dilthey, which is often used to analyze religious texts of puritan groups using an interpretative approach. In addition, we also conducted observations using non-participatory methods in communities that claim to be Salafi. This study states that Salafis's theology is very rigid and tends only to understand the text according to personal interpretation. This study also finds that people do not really understand the teachings of Salafis as a whole but only take refuge behind the name of Salafis. This research encourages the Ministry of Religion and MUI to be more active in maintaining unity in Islam, although there are some differences of opinion. And also encourage the public to enrich Islamic literature more to be more tolerant in understanding differences.